Reduced brain amyloid burden in elderly patients with narcolepsy type 1. Issue 1 (19th December 2018) - Gabelle, Audrey; Jaussent, Isabelle; Bouallègue, Fayçal Ben; Lehmann, Sylvain; Lopez, Régis; Barateau, Lucie; Grasselli, Caroline; Pesenti, Carole; de Verbizier, Delphine; Béziat, Séverine; Mariano‐Goulart, Denis; Carlander, Bertrand; et al.
Abstract : Objective: To determine whether brain amyloid burden in elderly patients with narcolepsy type 1 (NT1) is lower than in controls, and to assess in patients with NT1 the relationships between amyloid burden, cerebral spinal fluid (CSF) markers of Alzheimer disease (AD), CSF orexin‐A, and cognitive profile. Methods: Cognitive and 18 F‐florbetapir positron emission tomography (PET) data were compared in patients with NT1 aged ≥ 65 years (n = 23) and in age‐ and sex‐matched controls free of clinical dementia selected from the Alzheimer's Disease Neuroimaging Initiative (ADNI; n = 69) and the Multi‐Domain Intervention Alzheimer's Prevention Trial (MAPT‐18F AV45‐PET; n = 23) cohorts. The standardized uptake values (SUVs) of the cortical retention index for 6 regions of interest were computed and averaged to create a mean SUV ratio normalized to 3 subcortical reference regions (cerebellum, pons, and a composite region). A cortical/cerebellum SUV ratio ≥ 1.17 defined positive PET amyloid. Results: Lower cortical amyloid burden was observed in the NT1 than in the ADNI and MAPT‐AV45 groups (mean cortical/cerebellum SUV ratios = 0.95 ± 0.15, 1.11 ± 0.18 [ p < 0.0001], and 1.14 ± 0.17 [ p = 0.0005], respectively). Similar results were obtained with all subcortical reference regions and for all cortical regions of interest, except cingulum. Only 1 patient with NT1 (4.4%) had positive PET amyloid compared with 27.5% in the ADNI and 30.4% in the MAPT‐AV45 group. In the NT1 group, cortical or regional amyloid load was not associated with CSF orexin‐A, CSF AD biomarkers, or neuropsychological profile. Interpretation: Lower brain amyloid burden, assessed by 18 F‐florbetapir PET, in patients with NT1 suggests delayed appearance of amyloid plaques.ANN NEUROL 2019;85:74–83.